Current practice and registration patterns among United Kingdom Haemophilia Centre Doctors' Organisation centers for patients with unclassified bleeding disorders. (25th August 2021) - Thomas, Will; Downes, Kate; Evans, Gillian; Gidley, Gillian; Lowe, Gill; MacDonald, Stephen; Obaji, Samya; O'Donnell, James S.; Palmer, Ben; Pinto, Fernando; Desborough, Michael
Abstract: Background: Bleeding of unknown cause (BUC) and unclassified bleeding disorders (UBD) are increasingly recognized. There is no guidance on diagnosis and management. Objectives: To examine UK haemophilia centre registration patterns and current practice for UBD patients. Methods: In a two‐step process, the UK National Haemophilia Database (NHD) was reviewed for registration patterns of UBD patients and a survey of UK haemophilia centers was conducted (January/February 2021) to capture current practice for diagnosis and management of patients with UBD. Results/discussion: Overall, registrations with the NHD for UBD patients has sharply risen from 2012 to 2020 and in 2019 accounted for 2.65% of registered patients. For the survey, the response rate was 52/67 (78%). Practice was widely variable; 35/52 (67%) centers register UBD; among these 35 centers, terminology included UBD (28 centers), undiagnosed bleeding disorder (four centers), and BUC (three centers); 34/52 (65%) centers use a formal bleeding assessment tool. For management of dental extraction and high bleeding risk surgery in a fictional UBD patient we found that tranexamic acid was widely used; however, beyond this a variety of hemostatic products were advised including blood products, recombinant factor VIIa/prothrombin complex concentrate, and desmopressin. There was general consensus (≈90%) on avoiding regional anesthesia in pregnancy, but no agreement on the need for fetal precautions to avoid bleeding at delivery (50% would advise these). There was a disparity of opinion on chemical thromboprophylaxis, and management of patients without prior hemostatic challenges and offspring of these patients. Conclusion: This study provides a snapshot of current practice and real‐world data in this area. Future studies need to address the gaps in evidence.